무인선의 도킹을 위한 유도법칙 설계 - 우주현(Joohyun Woo); 김낙완(Nakwan Kim) (Han-guk haeyang gonghak hoeji (Online), 2016)
This paper proposes a potential field-based guidance law for docking a USV (unmanned surface vehicle). In most cases, a USV without side thrusters is an under-actuated system. Thus, there are undockable regions near docking stations where a USV cannot dock to a docking station without causing a collision or backward motion. This paper suggest a guidance law that prevents a USV from enter such a region by decreasing the lateral error to the docking station at the initial stage of the docking process. A Monte-carlo simulation was performed to validate the performance of the proposed method. The proposed method was compared to conventional guidance laws such as pure pursuit guidance and pure/lead pursuit guidance. As a result, the collision angle and lateral distance error of proposed method tended to have lower values compared to conventional methods.